2021
DOI: 10.1136/bmjopen-2021-056436
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 outcomes among adult patients treated with long-term opioid therapy for chronic non-cancer pain in the USA: a retrospective cohort study

Abstract: ObjectivePatients treated with long-term opioid therapy (LTOT) are known to have compromised immune systems and respiratory function, both of which make them particularly susceptible to the SARS-CoV-2 virus. The objective of this study was to assess the risk of developing severe clinical outcomes among COVID-19 non-cancer patients on LTOT, compared with those without LTOT.Design and data sourcesA retrospective cohort design using electronic health records in the TriNetX research database.Participants and setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 31 publications
1
20
2
Order By: Relevance
“…A full text review of the remaining 52 studies was then conducted, and 47 records were eliminated since they were reviews, abstract, letters, conferences, without comparison between opioid use and no-opioid use, or without clinical outcomes reported. Therefore, a total of 5 studies with 1,023,224 patients were included in the final analysis [ [22] , [23] , [24] , [25] , [26] ]. The process of study retrieval is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A full text review of the remaining 52 studies was then conducted, and 47 records were eliminated since they were reviews, abstract, letters, conferences, without comparison between opioid use and no-opioid use, or without clinical outcomes reported. Therefore, a total of 5 studies with 1,023,224 patients were included in the final analysis [ [22] , [23] , [24] , [25] , [26] ]. The process of study retrieval is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“… Study Region Opioid No opioid Study design Sample size Definition of opioid Adjusted variables NOS score Age Male (%) Age Male (%) Allen [ 22 ] 2020 U.S.A NR NR NR NR Retrospective cohort 11,830 ICD-10 codes F11 (opioid use disorder) Sex, age, race and comorbidity 8 Oh [ 23 ] 2021 South Korea NR NR NR NR Retrospective cohort 7713 All opiates except codeine, dihydrocodeine, hydrocodone, and tramadol. Sex, age, race, annual income level in 2020 and comorbidity 8 Qeadan [ 24 ] 2021 U.S.A 60 (48–70) 502 (49.6) 53 (35–68) 25,298 (49.3) Retrospective cohort 52,312 Measured by past opioid overdose or opioid use disorders recorded in ICD-9 or ICD-10 codes Age, gender, race/ethnicity, insurance, region, diabetes mellitus, asthma, hypertension, hydroxychloroquine, remdesivir, decadron or prednisone, aspirin and plavix 8 Tuan [ 25 ] 2021 U.S.A 52.1 ± 17.1 3764 (39.4) 43.1 ± 17.6 199,947 (48.9) Retrospective cohort 418,216 Individuals are prescribed with opioids in three or more consecutive months or at least 90 days at outpatient settings. Age, sex, race/ethnicity and comorbidities (diabetes, essential hypertension, chronic pulmonary conditions, cardiovascular diseases, mental health disorders) 8 Wiener [ 26 ] 2021 U.S.A 71.8 ± 6.3 3382 (45.1) 74.1 ± 7.3 245,186 (46.9) Retrospective cohort 533,153 The unhealthf...…”
Section: Resultsmentioning
confidence: 99%
“…High doses of opioids might exacerbate the respiratory depression found in COVID-19 patients and their chronic use can trigger opioid tolerance [ 8 ]. The higher doses used during the pandemic might result in greater adverse effects and increased risk of COVID-19 infection and mortality [ 9 11 ]. Opioid use disorders have, therefore, been targeted as a population at a particular risk of COVID-19 mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The study population consisted of adults (age≥18 years) with ADHD and COVID-19 infection. They were considered to have COVID-19 based on the presence of the ICD-10 diagnostic codes or positive laboratory test results confirming COVID-19 during the 18-month study assessment period (January 1, 2020-June 30, 2021; see Table A.1 for details) ( Tuan et al, 2021 ). Because an individual could have experienced a COVID-19 infection more than once, the first COVID-19 infection episode during the study assessment period was considered the “index” infection.…”
Section: Methodsmentioning
confidence: 99%
“…The available demographic data included sex (male/female), age, ethnicity (Hispanic/non-Hispanic) and race (White/Black/Other). Data on conditions known to be associated with the COVID-19 illness severity and/or ADHD outcomes included the diagnoses of medical conditions (obesity, diabetes, chronic kidney disease, cardiovascular disorders), ( Yek et al, 2022 , Tuan et al, 2021 ) mental health disorders (depression, anxiety, bipolar), ( Wang et al, 2021a ) and SUDs (tobacco/nicotine, alcohol, cannabis, cocaine, stimulant, opioid) ( Wang et al, 2021b ). Because the ‘current status’ of tobacco use/smoking was unavailable in the TriNetX database, the presence of the tobacco/nicotine use disorder diagnoses was used as the proxy of smoking/tobacco use.…”
Section: Methodsmentioning
confidence: 99%